FRI0207 Assessment of trio as the candidate gene for familial chondrocalcinosis ccal2. (1st June 2001) - Pendleton, A; Wright, GD; Doherty, MD; Shiang, R; Hughes, AE
Abstract : Background: Chondrocalcinosis is usually caused by the deposition of calcium pyrophosphate crystals on articular cartilage. There is a clear relationship between this crystal deposition and excess extracellular triphosphate and pyrophosphate. TRIO, a novel multidomain transmembrane protein which promotes the exchange of guanine diphosphate for guanine triphosphate in the extracellular space is an excellent positional candidate gene for CCAL2. Objectives: Methods: A positional candidate gene strategy was employed as a valid approach to identify the putative disease locus for CCAL2. The Online Mendelian Inheritance in Man OMIM cytogenetic map was used to identify TRIO as a possible candidate gene within the critical region on chromosome 5p. Mutation analysis required the design of PCR primers to amplify the coding DNA from human genomic DNA in affected individuals. The coding DNA sequence for TRIO was known 1 but information on the intron-exon splicing sequences was unavailable. Sotgun sequence obtained from a P1-derived artificial chromosome (PAC) 514p4 from a PAC contig of the critical region had shown homology with TRIO using the homology search algorithms BLASTN. The intron-exon junctions were identified from this PAC and other adjacent PACs on the contig, using a combination of vectorette PCR and the Genome Priming System (New England Biolabs inc) followed by Big Dye Terminator sequencing on an 377 ABI genetic analyser. Results: From the TRIO coding DNA sequence of 9 kilobases over 55 exons were identified. Both of the functional guanine exchange factor (GEF) domains (18 exons) have been fully sequenced but no mutations have yet been identified in affected members from two large families. Conclusion: TRIO is a novel multidomain transmembrane protein which is localised within the CCAL2 region on chromosome 5p. It is likely to influence the availability of extracellular triphophate and thus pyrophosphate through the function of the active GEF domains. This gene however has no mutations within the coding regions for both the GEF domains in two large kindreds with familial chondrocalcinosis. Reference: Debant A, Serra-Pages C, Seipel K, O'Brien S, Tang M, Park S-H, et al . The multidomain protein Trio binds the LAR transmembrane tyrosine phosphatase, contains a protein kinase domain, and has a separate rac-specific and rho-specific guanine nucleotide exchange factor domains. Proc Natl Acad Sci USA 1996;93:5466–71